KAJIAN PENGARUH SEL IMOBIL Arthrobacter NRRL B-3728 TERHADAP AKTIVITAS DAN STABILITAS ENZIM GLUKOSA ISOMERASE - Triantarti Triantarti; Hendro Santoso M (BERITA BIOLOGI, 2002)
This project focused on the immobilization of glucose isomerase (GI) from Arthrobacter B-3728. The whole cells immobilization technique using glutaraldehyde and gelatine type B220 was used in this research. The optimum time for harvesting Arthrobacter cells was determined before immobilization.The Arthrobacter cells were harvested after 56-72 h fermentation when the GI activity reaching 0.515-0.603 U/ml broth. The best treatment for cell immobilization was found using 5% gelatine when the GI activity reaching 0,888 U/ g immobilized cells. The optimum pH was not changed (pH 8) but the sensitivity to the pH was changed for immobilized cells compared to the free cells. However, the stability of the immobilized cells was lower compared to the free cells for long isomerization process. Further research are still needed for the development of immobilization technique for Arthrobacter B-3728.